Tinjauan Etika Kristen Terhadap Hak Azasi Anak dan Tanggung Jawab Orangtua Terhadap Anak dalam Keluarga Kristen (International Forum of Researchers and Lecturers, 2025)
This research examines the relationship between Christian ethics, children's human rights, and parental responsibilities in the context of Christian families. Referring to ethical principles ethical principles derived from the Bible, this study highlights the importance of recognising children's children's rights as a mandate from God that must be protected and honoured by parents. Through a theological approach, this article explores how parents can fulfil their responsibilities in educating and raising children with love, justice and integrity. It also examines the challenges faced by Christian families in implementing Christian ethical values in the midst of changing social dynamics. Christian ethical values in the midst of changing social dynamics. By emphasising the importance of moral and spiritual education, this article aims to provide guidance for parents in fulfilling children's rights and creating a family environment that supports the growth of character in accordance with the teachings of Christ. The results are expected to contribute to a better understanding of the role of parents in the context of children's human rights and Christian ethics, and the implications for contemporary family life.